Photocurrent Stimulation in Organic Photodiodes via Electrically Integrated Photon Energy Up-Conversion Organic Layers - Antoniou, Giannis N.; Yuan, Peisen; Keivanidis, Panagiotis E. (My University, 2021)
The photophysical process of low photon energy up-conversion via triplet-triplet annihilation (TTA-UC) describes the capability of a multicomponent system to exhibit photoluminescence (PL) at wavelengths shorter than the wavelength used for its photoexcitation. Systems exhibiting TTA-UC luminescence are particularly attractive to a broad range of light management applications including sensitization of photodiode devices, activation of photocatalytic systems and photo-stimulation of optogenetic platforms. Particularly for the area of organic solar cell (OSC) and organic photodetector (OPD) devices, TTA-UC offers the possibility to generate photocurrent when low energy photons are interacting with the device, which would be otherwise lost by their transmission through the device photoactive layer. However, to integrate a TTA-UC layer both by optical and electrical means into an organic photodiode device architecture remains challenging. Here we present a methodology that enables the generation of TTA-UC induced photocurrent in OPD devices functionalized with an electrically and optically integrated TTA-UC layer. An interlayer of the organometallic sensitizer of (2, 3, 7, 8, 12, 13, 17, 18-octaethyl-porphyrinato) PtII (PtOEP) is used for extending the absorption profile of a planar OPD heterojunction to the red, thereby allowing for the capture of photons with energies lower than the absorption energy of the heterojunction. Planar OPD heterojunctions are used comprising the 9,10 diphenyl anthracene (DPA) electron donor interfaced with a C60 fullerene acceptor. In respect to the DPA/C60 reference system, a 7-fold enhancement is achieved in the photocurrent of the PtOEP/DPA/C60 device when photons of 532 nm are used. In addition, the electrical integration of the PtOEP interlayer in the device structure facilitates an optimum hole extraction thereby generating an open circuit voltage of 500 mV. Time-integrated PL spectroscopy on the fabricated devices confirms the occurrence of the TTA-UC process that manifests in detection of the characteristic DPA luminescence upon laser excitation at 532 nm. The applicability of our methodology to a wider set of materials is demonstrated by replacing the C60 acceptor with bis(8-hydroxy-2-methylquinoline)-(4-phenylphenoxy)aluminum (BAlq), a high-energy gap electron acceptor. Based on these findings we demonstrate TTA-UC sensitized PtOEP/DPA/C60 OPD heterojunctions with responsivity (R), noise-equivalent power (NEP) and specific detectivity (D*) values of R= 610 μA/W, NEP= 40 pW and D*= 5.8 × 109 Jones at 550 nm. We will discuss on the potential utilization of these devices in all-optically ternary logic circuits and TTA-UC sensitized OSC platforms. This work was co-funded by the European Regional Development Fund and the Republic of Cyprus through the Research and Innovation Foundation (Project: EXCELLENCE/1216/0010).
Keywords: Photophysical process; Organic solar cell; Organometallic sensitizer